Cardiac Hypertrophy in Pregnant Rats, Descendants of Fructose-Fed Mothers, an Effect That Worsens with Fructose Supplementation - Cristina Donis; Elena Fauste; Madelín Pérez-Armas; Paola Otero; María I. Panadero; Carlos Bocos (Foods)
The role of fructose consumption in the development of obesity, MetS, and CVD epidemic has been widely documented. Notably, among other effects, fructose consumption has been demonstrated to induce cardiac hypertrophy. Moreover, fructose intake during pregnancy can cause hypertrophy of the maternal heart. Our previous research has demonstrated that maternal fructose intake has detrimental effects on fetuses, which persist into adulthood and are exacerbated upon re-exposure to fructose. Additionally, we found that maternal fructose consumption produces changes in female progeny that alter their own pregnancy. Despite these findings, fructose intake during pregnancy is not currently discouraged. Given that cardiac hypertrophy is a prognostic marker for heart disease and heart failure, this study aimed to determine whether metabolic changes occurring during pregnancy in the female progeny of fructose-fed mothers could provoke a hypertrophic heart. To test this hypothesis, pregnant rats from fructose-fed mothers, with (FF) and without (FC) fructose supplementation, were studied and compared to pregnant control rats (CC). Maternal hearts were analyzed. Although both FF and FC mothers exhibited heart hypertrophy compared to CC rats, cardiac DNA content was more diminished in the hearts of FF dams than in those of FC rats, suggesting a lower number of heart cells. Accordingly, changes associated with cardiac hypertrophy, such as HIF1α activation and hyperosmolality, were observed in both the FC and FF dams. However, FF dams also exhibited higher oxidative stress, lower autophagy, and decreased glutamine protection against hypertrophy than CC dams. In conclusion, maternal fructose intake induces changes in female progeny that alter their own pregnancy, leading to cardiac hypertrophy, which is further exacerbated by subsequent fructose intake.